2015
DOI: 10.3415/vcot-14-12-0188
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of three pre- and intraoperative measurement techniques for osteotomy positioning in the tibial plateau levelling procedure

Abstract: Preoperative measuring for planning a TPLO osteotomy is recommended. Techniques A and B in the current study were clinically practical and significantly more accurate compared to technique C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…A recent study investigated various techniques and their influence on the accuracy of tibial osteotomy position (33). The technique used in the current study was not investigated in that study or compared to other methods previously described, which is a limitation of the current study (27,33,34). Accuracy of the ICO may have been improved by the use of intra-operative fluoroscopy, however financial and time costs may be associated with the use of additional equipment.…”
Section: Number Of Stiflesmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study investigated various techniques and their influence on the accuracy of tibial osteotomy position (33). The technique used in the current study was not investigated in that study or compared to other methods previously described, which is a limitation of the current study (27,33,34). Accuracy of the ICO may have been improved by the use of intra-operative fluoroscopy, however financial and time costs may be associated with the use of additional equipment.…”
Section: Number Of Stiflesmentioning
confidence: 96%
“…Theoretically, multiple intraoperative measurements would improve accuracy through 'triangulation' . A recent study investigated various techniques and their influence on the accuracy of tibial osteotomy position (33). The technique used in the current study was not investigated in that study or compared to other methods previously described, which is a limitation of the current study (27,33,34).…”
Section: Number Of Stiflesmentioning
confidence: 98%
“…In this study, specific preoperative measurements were not made for osteotomy placement. Previous studies have shown that preoperative measurements for osteotomy placement can improve accuracy . Although such measurements may have improved osteotomy positioning, they were omitted as the authors have found that they are often omitted in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that preoperative measurements for osteotomy placement can improve accuracy . Although such measurements may have improved osteotomy positioning, they were omitted as the authors have found that they are often omitted in clinical practice. Lastly, in a cadaver study, proper placement of the proximal jig pin and alignment of the osteotomy with the jig pins is easier as more soft tissue can be removed.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a jig to guide the osteotomy was based on surgeon preference. The size of the osteotomy was dependent mainly on D1 measurement, striving for a minimum of 10 mm, as previously described . The osteotomy was stabilized with one of 6P, 8P, or 8AP fixation systems.…”
Section: Methodsmentioning
confidence: 99%